2009
DOI: 10.4049/jimmunol.0803977
|View full text |Cite
|
Sign up to set email alerts
|

P2Y 2 Receptor Transcription Is Increased by NF-κB and Stimulates Cyclooxygenase-2 Expression and PGE2 Released by Intestinal Epithelial Cells

Abstract: Inflammatory stresses associated with inflammatory bowel diseases up-regulate P2Y2 mRNA receptor expression in the human colon adenocarcinoma cell line Caco-2, the noncancerous IEC-6 cells and in colonic tissues of patient suffering from Crohn’s disease and ulcerative colitis. However, the transcriptional events regulating P2Y2 receptor (P2Y2R) expression are not known. We have identified a putative transcription start site in the P2Y2R gene and demonstrated acetylation of Lys14 on histone H3 and Lys8 on histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 56 publications
(84 reference statements)
9
73
0
Order By: Relevance
“…Activation of the P2X7R in microglia promotes the release of IL-1β, TNF-α, and ATP [16,75,105,[154][155][156], suggesting a mechanism whereby the P2X7R regulates functional P2Y 2 R expression in neurons and other cells. The finding that P2Y 2 R expression under proinflammatory conditions is regulated by NF-κB binding to the P2Y 2 R promoter [104] is consistent with the established role of NF-κB activation in the induction of inflammation [157].…”
Section: P2y 2 Receptors In Neuronssupporting
confidence: 84%
See 1 more Smart Citation
“…Activation of the P2X7R in microglia promotes the release of IL-1β, TNF-α, and ATP [16,75,105,[154][155][156], suggesting a mechanism whereby the P2X7R regulates functional P2Y 2 R expression in neurons and other cells. The finding that P2Y 2 R expression under proinflammatory conditions is regulated by NF-κB binding to the P2Y 2 R promoter [104] is consistent with the established role of NF-κB activation in the induction of inflammation [157].…”
Section: P2y 2 Receptors In Neuronssupporting
confidence: 84%
“…In rPCNs, P2Y 2 R expression is relatively low but is significantly upregulated by IL-1β via a pathway that involves the activation of the transcription factor NF-κB [48]. Indeed, it has been shown that the P2Y 2 R promoter contains a NF-κB binding sequence that is required for inflammation-induced P2Y 2 R upregulation, a pathway that can be blocked by Bay-11-7085, a specific inhibitor of the phosphorylation of IκB-α, the endogenous regulator of NF-κB activity [104]. Thus, it seems likely that the co-release of IL-1β and nucleotides mediated by ATP-induced P2X7R activation in microglia [16,75,105] provides an in vivo mechanism for both the upregulation and activation of P2Y 2 Rs in neurons and other cell types.…”
Section: P2y 2 Receptor Signaling Pathwaysmentioning
confidence: 99%
“…It is possible that injured ISMFs may significantly jpet.aspetjournals.org increase the secretion of PGE 2 to promote wound healing and the concentration at the edge of the wound may reach more than 0.42 M. We have focused here on the role of ISMFderived PGE 2 . However, epithelial cells or immune cells infiltrating into the lamina propria during inflammation also secrete PGE 2 (Bowman and Bost, 2004;Degagné et al, 2009). PGE 2 released from these cells may also contribute to ISMF wound healing in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular mechanisms and components that enhance the formation of these acinar-like aggregates would likely be important factors in salivary gland reconstitution and regeneration. In this study, we investigated the role in salivary gland reconstitution/regeneration of the P2Y 2 nucleotide receptor (P2Y 2 R) for extracellular ATP and UTP, since previous findings have suggested roles for the P2Y 2 R in corneal epithelia wound healing by inducing cell migration (119), liver regeneration by promoting hepatocyte proliferation (8), inflammatory bowel disease by enhancing epithelial repair (27), intestinal reepithelialization following experimental colitis (26), and reduction of infarct size following myocardial infarction (20). In addition, the P2Y 2 R is upregulated upon disruption of salivary gland tissue homeostasis (113) and in salivary glands of the NOD.B10 mouse model of SS-like autoimmune exocrinopathy (99).…”
mentioning
confidence: 99%